Fabrication of an electrochemical sensor based on magnetic multi-walled carbon nanotubes for the determination of ciprofloxacin. Issue 16 (13th April 2016) - Bagheri, H.; Khoshsafar, H.; Amidi, S.; Hosseinzadeh Ardakani, Y.
Abstract : Fabrication of an electrochemical sensor based on a composite of magnetic multi-walled carbon nanotubes – molecularly imprinted polymer for the determination of ciprofloxacin. Abstract : We have developed a novel and efficient electrochemical sensor to measure ciprofloxacin using a composite of magnetic multi-walled carbon nanotubes (MMWCNTs) and molecularly imprinted polymer (MIP). Magnetic MIP (MMIP) capable of selectively responding to ciprofloxacin was successfully synthesized by a simple method. The characterization of the imprinted composite was carried out by scanning electron microscopy (SEM), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The performance of the carbon paste electrode modified with MMIP was investigated using cyclic voltammetry and differential pulse voltammetry to detect ciprofloxacin selectively. The detection limit of this method was determined to be 0.0017 μmol L −1 with a linear detection range (3 S b / m ) of 0.005–0.85 μmol L −1 . This method proved to be a simple, selective and rapid way of determining ciprofloxacin in pharmaceutical samples and biological fluids. It has potential applications in routine analysis with high specificity, excellent reproducibility, and good stability.